KEPASTIAN HUKUM PENERAPAN KRITERIA PENYIDIKAN PERKARA TINDAK PIDANA KORUPSI OLEH KOMISI PEMBERANTASAN KORUPSI REPUBLIK INDONESIA - Lambertus Josua Tallaut; Ade Adhari (Jurnal Hukum Adigama, 2021)
The authority to investigation corruption cases is owned by the Corruption Eradication Commission, the Attorney General’s Office and the Police. To guarantee legal certainty in the exercise of athority, Article 11 of the KPK Law provides for the investigation of corruption cases which are under the authority of the KPK. In practice, this Article is not carried out in a consistent and obedient manner, such as the Jiwasraya, case, the Pinagki Prosecutor and the North Minahasa Ready-to-Use Fund Corruption which were investigated by the Prosecutor’s Office, in thes three cases the authority of the KPK. This phenomena creates legal uncertainty, even though certainty as a legal value must be upheld. The research method used is juridical-normative with primary and secondary legal materials as material for obtaining secondary data. The data was obtained by library technique and analyzed by descriptivequalitative method. Legal certainty is domiciled as a legal value, which means that the purpose of law is legal certainty. Legal certainty is also an important element in the administration of a state of law, therefore Indonesia is obliged to uphold legal certainty in implementation activities, including taking action against corruption cases. The criteria for the KPK authority case investigated by the Prosecutor's Office create legal uncertainty regarding the application of Article 11 of the KPK Law. Prosecutors' actions are also theoretically authoritative, exceeding their authority.